(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Evaluating the change in hemodynamic of patients with multiple traumatic shock flolowing the guidelines of transpulmonary thermodilution (PiCCO) at Bac Ninh General Hospital. Subjec and methods: The descriptive prospective, 30 patients were diagnosed with multiple traumatic shock, is treated according to management guidelines based on hemodynamic parameters PiCCO at Bac Ninh General Hospital. Record hemodynamic parameter through PiCCO at the time of PiCCO catheter insersion (T0), after 6 hours (T6), after 12 hours (T12), after 24 hours (T24), after 48 hours (T48) and after 72 hours (T72). Regulate hemodynamics using fluid infusion, blood transfusion and vasopressors. Results: Among 30 patients: 22 males, 8 females. The lowest age was 16 years old, the highest age was 90 years old. At the time T0, The GEDI index is 547.5 ± 163.2 ml/kg, SVRI index is 2103.2 ± 720.0 dyne.s.cm-5m-2, CI index is 3.56 ± 0.97 ml/kg/m2 and ELWI is 7.9 ± 2.3 ml/ kg. The GEDI index and CI at subsequent time points increased compared to the initial period with statistical significance with p < 0.05. The ELWI index increased but all times were below 10 ml/kg. Conclusions: Hemodynamic in patients with multiple traumatic shock is unstable in the first 6 hours and gradually stabilizes in the following periods when hemodynamic adjustment methods are used.